Avaliação da estabilidade oxidativa do óleo bruto de açaí (Euterpe oleracea) na presença de compostos fenólicos puros ou de extratos vegetais amazônicos - Jonas Joaquim Mangabeira da Silva (Química Nova, 2013)
A final 241 µM of ascorbyl palmitate and 555 µM of the following antioxidants separately: BHA, myricetin and quercetin standards, and extracts of Byrsonima crassifolia, Inga edulis or Euterpe oleracea, were added to crude açai oil and submitted to the oxidation process at 60 ºC for 11 days. Among the antioxidants used, only the myricetin standard showed the ability to defer the oxidation process until the third day of treatment. B. crassifolia, I. edulis and E. oleracea extracts showed no preventive capacity against the oxidation process, despite their high concentration phenolic compounds and antioxidant activities.